Determinasi Demografi terhadap Perilaku Karitatif Keorganisasian - Slamet S. Sarwono; Amiluhur Soeroso (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2001)
This study examined the influence of demographic characteristics toward organizational citizenship behavior (OCB). Data were obtained from employees of medical-care industries with the aid of the structured questionnaire. In this research, data is processed with multiple regression technique. The result indicates that occupancy and marriage were negatively influence OCB, whereas education, tenure, job status and sex are not.Keywords: demography, inference, organizational citizenship behavior (OCB).